Changes in phenology mediate vertebrate population responses to temperature globally - Radchuk, Viktoriia; Jones, Carys V.; McLean, Nina; Charmantier, Anne; Teplitsky, Céline; Alisauskas, Ray; Ancona, Sergio; Anker-Nilssen, Tycho; Arcese, Peter; Arlt, Debora; Aubry, Lise M.; Bailey, Liam; et al. (Springer Nature, 2026)
Phenotypic responses to climate affect individual fitness, but the extent to which this translates into effects on population dynamics remains poorly understood. We assemble 213 time series on phenotypes and population sizes of wild vertebrates globally and match them with local climate data. Our meta-analysis shows that morphological traits are mostly climate insensitive. However, phenology is earlier in warmer-than-average years, which contributes positively to population growth in most species. At lower latitudes, temperature has weaker effects on phenology but stronger direct negative effects on population growth, likely because these populations are less capable of tracking climate via plasticity. Variation in the phenology-mediated effect of temperature on population growth cannot be explained by latitude, generation time, migratory mode, or diet. This suggests that simple relationships between species characteristics and population responses to warming may not occur in nature. Instead, we may need to embrace ecological complexity by considering local-scale predictors that capture intra-specific variation.